Asosiasi Lalat Buah (Bactrocera spp.) (Diptera : Tephritidae) dan Parasitoidnya pada Tanaman Jambu Biji Kristal (Psidium guajava L.) yang Dibudidayakan di Bali - I WAYAN DEDI ADNYANA; NI NENGAH DARMIATI; DWI WIDANINGSIH (Agrotrop : Journal on Agriculture Science, 2019)
Association of Fruit Flies (Bactrocera spp.) (Diptera: Tephritidae) and Their Parasitoid on Guava (Psidium guajava L.) Cultivated in Bali. The study on the association of fruit flies (Bactrocera spp.) (Diptera: Tephritidae) and their parasitoid on guava (Psidium guajava L.) cultivated in Bali was conduted in order to know the abundance, attacks percentage and the species of parasitoid associated on guava, cultivated in Bali. The sampling was done intentionally by taking attacked fruit in Musi Village, Buleleng Regency; Pelaga Village, Badung Regency; and Tiga Village, Bangli Regency. The results showed that 3 species of fruit flies were found, namely B. carambolae, B. papayae and B. albistrigata. The percentage and number of adult insect emergence in Musi Village were B. papayae (50.87% ; 2772 imago), B. carambolae (35.18% ; 1803 imago) and B. albistrigata (13.94% ; 741 imago). In Pelaga Village B. carambolae (61.31% ; 2864 imago) dominates and B. papayae only 38.69% and 1801 imago. B. carambolae is also found dominant in Tiga Village (59.08% ; 2303 imago) and B. papayae only 40.92% and 1603 imago. Percentage of damage to guava is 24.27% on average. There are three species of parasitoids found that are associated with fruit flies on guava in Bali, namely Fopius arisanus, Diachasmimorpha sp. and Opius sp. The average parasitic rate is 6.76%. The highest parasitic rate is in Musi Village, Buleleng while the lowest is in Tiga Village, Bangli.